2016
DOI: 10.1371/journal.pone.0154061
|View full text |Cite
|
Sign up to set email alerts
|

Biochar, Bentonite and Zeolite Supplemented Feeding of Layer Chickens Alters Intestinal Microbiota and Reduces Campylobacter Load

Abstract: A range of feed supplements, including antibiotics, have been commonly used in poultry production to improve health and productivity. Alternative methods are needed to suppress pathogen loads and maintain productivity. As an alternative to antibiotics use, we investigated the ability of biochar, bentonite and zeolite as separate 4% feed additives, to selectively remove pathogens without reducing microbial richness and diversity in the gut. Neither biochar, bentonite nor zeolite made any significant alterations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 54 publications
3
51
0
1
Order By: Relevance
“…Teleb, Hegazy, and Hussein (2004) found that supplementing broiler diets with 0.5% biochar reduced the detrimental effects of aflatoxins, lowering mortality and improving growth performance. Prasai et al (2016) and revealed that biochar reduced the pathogenic bacterium Campylobacter jejuni in pullets' gut microbiota. In in vitro uremic toxin (urea and creatinine) adsorption model experiments, Jandosov et al (2017) found that rice husk-derived carbon enterosorbents (biochar) modified by oxidation by ozone followed by ammonia treatment of the carbon surface were able to reduce clinically significant levels of uremic toxins, comparable to commercial enterosorbents.…”
Section: Removal Of Pollutants and Toxins In Animalsmentioning
confidence: 99%
See 3 more Smart Citations
“…Teleb, Hegazy, and Hussein (2004) found that supplementing broiler diets with 0.5% biochar reduced the detrimental effects of aflatoxins, lowering mortality and improving growth performance. Prasai et al (2016) and revealed that biochar reduced the pathogenic bacterium Campylobacter jejuni in pullets' gut microbiota. In in vitro uremic toxin (urea and creatinine) adsorption model experiments, Jandosov et al (2017) found that rice husk-derived carbon enterosorbents (biochar) modified by oxidation by ozone followed by ammonia treatment of the carbon surface were able to reduce clinically significant levels of uremic toxins, comparable to commercial enterosorbents.…”
Section: Removal Of Pollutants and Toxins In Animalsmentioning
confidence: 99%
“…Since 2010, biochar has increasingly been used as a feed additive in animal husbandry (O'Toole et al, 2016). As shown in Table 1, biochar used as a feed supplement is commonly made from biomass such as rice husks (Leng et al, 2012;Phongpanith, Inthapanya, & Preston, 2013), woody green waste (Prasai et al, 2016), pine wood chips (Saleem et al, 2018) and jarrah wood (Joseph et al, 2015).…”
Section: Raw Materials Used For Production Of Biocharmentioning
confidence: 99%
See 2 more Smart Citations
“…Supplementation of contaminated diets with SB decreased transition of aflatoxin M1 to goat’s Milk [70]. Also bentonite has been used as bleaching [48], remove pathogens from the gastrointestinal of poultry [74], toxin binder [56], stabilization of sewage sludge containing heavy metals [49], buffering agent in feedstuffs [24], manipulation of a rumen ecosystem [39, 67] and performance of broiler chickens [55]. The performance of fattening Zandi lambs improved with the dietary inclusion of SB compared to control group [54] and also, fat-tail percentage decreased.…”
Section: Introductionmentioning
confidence: 99%